Preferensi Mahasiswa terhadap Desain Kantin yang Ideal Pascapandemi Covid-19 - Sidhi Pramudito; Rachmat Budihardjo (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2022)
This reserach was conducted to explore student preferences to formulate the ideal canteen design criteria in this post-pandemic period. The analytical method used in this study is a content analysis method with the stages of open coding, axial coding, and selective coding through the data obtained using an online questionnaire. Based on the analysis, it was found that the dominant factors that became student preferences for the ideal post-pandemic canteen design criteria were "cleanliness and health" and "spacious room". Several things that can be considered to support these criteria are the availability of hygiene and health facilities, smoke-free rooms (cooking and smoking), additional signage, distance between furniture and visitors, additional barriers, consideration of space capacity, good air circulation, and open design.